An extracellular matrix-mimicking, bilayered, heterogeneous, porous, nanofibrous scaffold for anterior urethroplasty in a rabbit model. (21st September 2020) - Wan, Xiang; Zheng, Dachao; Yao, Haijun; Fu, Shibo; Wei, Ziwei; Wang, Zhong; Xie, Minkai
Abstract: Anterior urethral reconstruction is still a challenging clinical task, and tissue engineering technology offers new options for anterior urethroplasty. In this work, we evaluated an extracellular matrix (ECM) mimicking scaffold for anterior urethral reconstruction in a New Zealand white rabbit model. After the creation of a urethral defect, the ECM-mimicking scaffold was applied in six rabbits, and small intestinal submucosa (SIS) was used in three rabbits. The outcomes of urethrography and histological analysis were evaluated six months postoperatively. A larger urethral diameter was observed in the ECM-mimicking scaffolds (3.01 ± 0.12 mm) than in the SIS grafts (0.95 ± 0.07 mm). Urethral fistulae and stenosis were observed in the SIS grafts. Urothelial and smooth muscle cells were observed in all rabbits, but the ECM-mimicking scaffold showed better performance. The ECM-mimicking scaffold may be an effective clinical treatment option for congenital and acquired urethral pathologies.